Transitions in Secondary Education in Sub-Saharan Africa : Equity and Efficiency Issues - Bregman, Jacob (Washington, DC : World Bank, 2012)
The main purpose of the Secondary Education in Africa (SEIA) -TRANSE study has been to identify and analyze measures that may lead to more efficient and equitable transitions in secondary education. These measures are on the one hand aiming at improving the structure and increasing the capacity of secondary education, and on the other hand to facilitate the individuals' possibilities to enter and to succeed in secondary education. Measures may be implemented at the national, regional or local level. Author especially focuses on measures like: (a) Financial (expansion of capacity, improvement of infrastructure, support to students); (b) Provisions (attractiveness and relevance, volume, location, quality and support, selection mechanisms); (c) Counseling; (d) PTA (parent teacher associations) and other local community and school relations; and (e) Reducing factors that are hindering youth to enter or to stay in schools. This paper synthesizes the findings of the country studies, highlighting the factors contributing to more equitable and efficient transitions in secondary education, and offers conclusions and recommendations.